1992
DOI: 10.1212/wnl.42.11.2207
|View full text |Cite
|
Sign up to set email alerts
|

Aphasic seizure caused by focal epilepsy in the left fusiform gyrus

Abstract: We report a patient with paroxysmal aphasia evoked by ictal epileptiform discharges localized to the left fusiform gyrus, where a small brain tumor existed. The intracranial EEG recordings during other seizures demonstrated a close functional link between the left fusiform gyrus and Wernicke's area. The patient also showed transient aphasia with electrical stimulation of the left fusiform gyrus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The long duration of the dysphasia, approximately a few weeks, was compatible with status epilepticus, and PLEDshave been recognized to represent status epilepticus on electroencephalograph (6). Epileptic dysphasia is a rare clinical condition (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and the present case is noteworthy because of the prolonged dysphasia with persistent PLEDswhich persisted throughout the recording time. Although Wells CR (19) reported a case of epileptic dysphasia and PLEDsappeared transiently in that case, noneof the previous cases of epileptic dysphasia were accompanied by persistent PLEDsas the present case.…”
Section: Discussionmentioning
confidence: 57%
“…The long duration of the dysphasia, approximately a few weeks, was compatible with status epilepticus, and PLEDshave been recognized to represent status epilepticus on electroencephalograph (6). Epileptic dysphasia is a rare clinical condition (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and the present case is noteworthy because of the prolonged dysphasia with persistent PLEDswhich persisted throughout the recording time. Although Wells CR (19) reported a case of epileptic dysphasia and PLEDsappeared transiently in that case, noneof the previous cases of epileptic dysphasia were accompanied by persistent PLEDsas the present case.…”
Section: Discussionmentioning
confidence: 57%
“…This relationship was quite consistent across participants. Dense anatomical connections are known to exist between basal temporal and temporoparietal areas (Luders et al, 1986;Suzuki, Shimizu, & Tani, 1992), and the relative timing observed between these two areas may depend on these connections. Activity in medial temporal areas was concurrent with that in temporoparietal areas, and careful inspection of the data suggested either a coincident or phasic relationship between activity in the two areas.…”
Section: Discussionmentioning
confidence: 99%
“…As an ictal phenomenon (during which the patient is alert but dysphasic) there is usually a correlation between the clinical seizure and simultaneous EEG changes, denoting corresponding electrical ictal activity that would cease once the clinical fit was over [9,10]. In our patient, however, such a pattern was not seen.…”
Section: Discussionmentioning
confidence: 57%
“…In relation to epilepsy, aphasia can be either a manifestation of an ictal as in partial complex seizures or a post-ictal phenomenon (todd phenomenon) [3,[9][10][11]. As an ictal phenomenon (during which the patient is alert but dysphasic) there is usually a correlation between the clinical seizure and simultaneous EEG changes, denoting corresponding electrical ictal activity that would cease once the clinical fit was over [9,10].…”
Section: Discussionmentioning
confidence: 99%